Issues, Challenges, and Potential of Palliative Care in Pediatric Nursing: A Systematic Review - Widiyanto, Aris; Handayani, Rina Tri; Atmojo, Joko Tri (Journal of Maternal and Child Health, 2020)
Background: Palliative care is an essential right for infants and children with a life-threaten